The Moderating Effect of Corporate Transparency on the Relationship between Audit Quality, Audit Committee, Ownership Structure, and Reporting Quality - Rizki Saputra; Umianty Hamzani; Muhammad Fahmi; Syarif Helmi; Nina Febriana Dosinta (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the moderating effect of corporate transparency on the relationship between audit quality, audit committee, and ownership structure on the quality of financial reporting in banking companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The research employs a quantitative method with data analysis conducted using SPSS version 25. The results indicate that audit quality and the audit committee have a significant effect on the quality of financial reporting. On the other hand, ownership structure does not have a significant effect on financial reporting quality. Corporate transparency is proven to moderate the influence of audit quality and the audit committee on financial reporting quality; however, transparency does not moderate the influence of ownership structure on financial reporting quality.